Wheat Fermentation With Enterococcus mundtii QAUSD01 and Wickerhamomyces anomalus QAUWA03 Consortia Induces Concurrent Gliadin and Phytic Acid Degradation and Inhibits Gliadin Toxicity in Caco-2 Monolayers - Sakandar, Hafiz Arbab; Kubow, Stan; Azadi, Behnam; Faryal, Rani; Ali, Barkat; Ghazanfar, Shakira; Quraishi, Umar Masood; Imran, Muhammad (Frontiers in Microbiology, 2019)
Foods containing high amounts of either phytic acid or gliadin can pose a risk for development of iron deficiency and celiac disease, respectively. Present study was conducted to evaluate the effects of preselected gliadin degrading strains, Enterococcus mundtii QAUSD01 and Wickerhamomyces anomalus QAUWA03, on phytic acid and gliadin degradation in six wheat cultivars (Lasani 2008, Seher 2006, Chakwal 97, Shafaq 2006, Bars 2009, Barani 83). In addition, tight junction proteins, trans-epithelial resistance (TER) and ruffle formation in Caco-2 cells was evaluated relative to S. cerevisie–mediated fermentation and unfermented controls. Phytic acid degradation as demonstrated was observed in all six cultivars fermented with E. mundtii QAUSD01 and W. anomalus QAUWA03 consortia. Among the six cultivars, Shafaq 2006 showed relatively higher degradation of gliadin. Relative to the other tested wheat varieties, Lasani 2006 showed minimal toxic effects on Caco-2 cells in terms of ruffle formation, tight junction proteins and TER values, which can be attributed to extensive degradation of toxic gliadin fragments.